Risk assessment in medically treated chronic thromboembolic pulmonary hypertension patients. Issue 5 (8th November 2018) - Delcroix, Marion; Staehler, Gerd; Gall, Henning; Grünig, Ekkehard; Held, Matthias; Halank, Michael; Klose, Hans; Vonk-Noordegraaf, Anton; Rosenkranz, Stephan; Pepke-Zaba, Joanna; Opitz, Christian F.; Gibbs, J. Simon R.; et al.
Abbreviated versions of the risk stratification strategy of the European Society of Cardiology (ESC)/European Respiratory Society (ERS) pulmonary hypertension guidelines have been recently validated in patients with pulmonary arterial hypertension. We aimed to investigate their prognostic value in medically treated chronic thromboembolic pulmonary hypertension (CTEPH) patients from the COMPERA registry, which collects six variables of interest (World Health Organization Functional Class, 6-min walk distance, brain natriuretic peptide, right atrial pressure, cardiac index and mixed venous oxygen saturation). We included patients with at least one follow-up visit, no pulmonary endarterectomy and at least three of the six variables available, and classified the patients into low-, intermediate- and high-risk groups. As a secondary analysis, the number of noninvasive low-risk criteria was counted. The association between risk assessment and survival was evaluated. Data from inclusion and follow-up (median 7 months) visits were available for 561 and 231 patients, respectively. Baseline 1- and 5-year survival estimates were significantly different (p<0.0001) in the baseline low-risk (98.6% and 88.3%, respectively), intermediate-risk (94.9% and 61.8%, respectively) and high-risk (75.5% and 32.9%, respectively) cohorts. Follow-up data were even more discriminative, with 100%, 92% and 69% 1-year survival, respectively. The number of low-risk noninvasive criteria was also associated with survival. These analyses suggest that the ESC/ERS risk assessment may be applicable in patients with medically treated CTEPH. The risk stratification for PAH of the current European PH guidelines may allow survival prediction in medically treated CTEPH patients http://ow.ly/zx5430lI41T